2020
DOI: 10.21203/rs.3.rs-105785/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of injectable corticosteroid for osteoarthritis of the first metatarsophalangeal joint 

Abstract: Intra articular steroid injection is a common treatment modality for relief of pain and inflammation associated with degenerative joint disease. Use of injectable steroid preparations is widely accepted as safe and effective for the treatment of osteoarthritis of the 1st metatarsophalangeal joint. Despite the frequency of use, literature specific to pathology of the 1st metatarsophalangeal joint is sparse. The aim of this systematic review was to determine if good quality research exists to enable clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The final count of papers utilised for review was 37. Iterative charting of the literature yielded three broad and overlapping themes: Nineteen articles are summarised Themes 1 and 2 (two articles appear in Theme 2 also) with a systematic review of the result of further work [69]. 20 articles (plus one, one unreferenced, and one found after the initial search) were technical/technique articles (Theme 2) and led to the development of a best practice IT guideline [100].…”
Section: Resultsmentioning
confidence: 99%
“…The final count of papers utilised for review was 37. Iterative charting of the literature yielded three broad and overlapping themes: Nineteen articles are summarised Themes 1 and 2 (two articles appear in Theme 2 also) with a systematic review of the result of further work [69]. 20 articles (plus one, one unreferenced, and one found after the initial search) were technical/technique articles (Theme 2) and led to the development of a best practice IT guideline [100].…”
Section: Resultsmentioning
confidence: 99%
“…Reilly et al 70 performed a systematic review to determine if good quality research exists to enable clinicians to adopt an evidence-based approach to 1 st MTP jt CSIs for OA. Despite the frequency of use, the review found no high-quality studies that support their use.…”
Section: Post-operative Arthrofibrosismentioning
confidence: 99%
“…Reilly et al (2020) performed a systematic review of injectable corticosteroid for OA of the 1 st MTP jt (Reilly at al, 2020). The aim of their review was to determine if good quality research exists to enable clinicians to adopt an evidenced based approach to corticosteroid injection (CSI) of the jt.…”
Section: Pathologymentioning
confidence: 99%
“…With the review by Reilly et al (2020) failing to produce strong evidence for the IA CSI of 1 st MTP jt OA, a scoping review was therefore considered to be the most suitable approach to answer the research question looking at the wider themes about injection therapy of this jt. (Levac et al, 2010).…”
Section: Munn Et Al (Munn Et Al 2018) Listed the Indications For Scoping Reviewsmentioning
confidence: 99%